The Manager's Answer Book - Mitchell, Barbara; Gamlem, Cornelia (Ascent Audio, 2018)
Congratulations, you're a manager! Of course you have expertise in the field you're managing, but what about everything else? There's so much more to know! Whether you're a new or seasoned manager, your responsibilities can become overwhelming at times. There are days and new situations that will leave you feeling vulnerable. You don't know where to start or even what to ask! The Manager's Answer Book can help. In question-and-answer format, this easy-to-use guide provides information on many aspects of managing. You will learn about: - Getting started: moving from peer to manager, setting goals, managing projects, resources, and much more. - Developing your management skills: communicating, delegating, motivating, and facilitating. - Building and managing your team: hiring, firing, and everything in between. - Creating your personal brand: building credibility for yourself, your team, and your department. - Managing up, down, and around: working with people and functions in your organization. - Potential land mines: conflict, change, and risk. - Legal pitfalls: navigating the miasma of laws and regulations.